How important are atmospheric depressions and mobile cyclones for emitting mineral dust aerosol in North Africa? - S. Fiedler; K. Schepanski; P. Knippertz; B. Heinold; I. Tegen (Atmospheric Chemistry and Physics, 2014)
This study presents the first quantitative estimate of the mineral dust emission associated with atmospheric depressions and mobile cyclones in North Africa. Atmospheric depressions are automatically tracked at 925 hPa based on ERA-Interim data from the European Centre for Medium-Range Weather Forecasts for 1989–2008. A set of filter criteria is applied to identify mobile cyclones, i.e. migrating and long-lived cyclones. The shorter term cyclone is used as a synonym for mobile cyclones. Dust emission is calculated with a dust emission model driven by 10 m winds and soil moisture from ERA-Interim. Emission peaks during winter and spring with spatial averages of 250–380 g m−2 per month. Comparison of the dust source activation frequency from the model against SEVIRI satellite observation shows a good agreement in the Bodélé Depression but differences in the north and west of North Africa. Depressions are abundant, particularly in summer when the Saharan heat low is situated over West Africa and during spring in the lee of the Atlas Mountains. Up to 90% (55% annually and spatially averaged) of dust emission occurs within 10 degrees of these depressions, with embedded mechanisms such as nocturnal low-level jets playing a role. Cyclones are rarer and occur primarily north of 20° N in spring in agreement with previous studies and over summertime West Africa consistent with near-surface signatures of African Easterly Waves. Dust emission within 10 degrees of cyclones peaks over Libya with up to 25% in spring. Despite the overall small contribution of 4% annually and spatially averaged, cyclones coincide with particularly intense dust emission events exceeding the climatological mean by a factor of four to eight. Soil moisture weakens dust emission during cyclone passage by about 10%.